Lightning Distribution in Tropical Cyclones Making Landfall in China - Zhang, Wenjuan; Zhang, Yijun; Shu, Shoujuan; Zheng, Dong; Xu, Liangtao (Frontiers in Earth Science, 2022)
Lightning data from the World Wide Lightning Location Network (WWLLN) are used to document the lightning characteristics in tropical cyclones (TCs) making landfall in China. The landfall period is confined to 48 h prior to and after landfall (t-24~t+24). Data from a total of 74 TCs are collected from 2010 to 2020, providing 3293 individual time periods (1-h periods). To examine the radial and asymmetry distributions as a function of TC intensity, landing location, and vertical wind shear, the dataset is classified into two intensity categories, three shear groups, and four landing locations. WWLLN detected lightning activity in all TCs during the 48-h landfall, with lightning rates most frequently appearing between 250 and 600 str h-1. Extreme hourly lightning rates of 3154 str h-1 and 4426 str h-1 are observed in the inner core in Tropical Storm Cimaron (2013) and the outer rainbands in Severe Typhoon Matmo (2014), respectively, comparable to lightning activity in mesoscale convection systems on land. TCs landing in Guangdong and Hainan have the largest peak lightning rates, while those landing in Zhejiang and Shanghai show the lowest lightning rates. The maximum lightning density is found in the inner core region of weak TCs (< 32.7 m s-1) that are located approximately 100-200 km away from the coastline. The radial distribution of lightning density at landing stages is consistent with that at mature stages when TCs are over the ocean. However, there is a shift in the lightning maximum from the inner core prior to landfall (t-24~t0) to the outer rainbands after landfall (t0~t+24), indicating the effects of dry continental air intrusion and the enhanced surface frictional convergence. Vertical wind shear is the dominant factor in producing lightning and convective asymmetry for TCs landing in all locations. Lightning asymmetries are enhanced with the increase in shear magnitude from low (< 5 m s-1) to moderate (5-10 m s-1) and high (> 10 m s-1) shear environments, both in weak and strong TCs (≥ 32.7 m s-1).